Pertanggungjawaban Pidana Notaris Dalam Perspektif Perbedaan Tindak Pidana dan Pelanggaran Administratif (Studi Putusan Mahkamah Agung Nomor 20 Pk/Pid/2020) - Nugroho, Adrelano Akbar (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
Notaries are authorized to draw up authentic deeds that have full probative force. However, in practice, problems often arise when deeds give rise to disputes, resulting in notaries being subject to criminal proceedings. This study aims to analyze the limits of notaries' criminal liability under Indonesian positive law and the legal construction based on the Notary Position Law (UUJN) and the Criminal Code (KUHP). The research method used is normative juridical through literature study and analysis of court decisions. The results show that notaries' liability is divided into administrative and criminal spheres. Criminal liability is only possible if there is intent or negligence that fulfills the elements of a crime, while administrative negligence must be resolved through the UUJN. Supreme Court Decision Number 20 PK/Pid/2020 confirms that criminal law is the ultimum remedium, so it is not appropriate to apply it to notary administrative errors.